2022
DOI: 10.2478/mmcks-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of brand personality dimension on consumer buying decision: evidence from Ghana

Abstract: With the advent of innovative marketing, the increasing use of brand personality concepts for the promotion of a brand or product has received scholarly work across the globe. Yet little is known in the literature about the dimensions of brand personality and its applicability in the telecommunication industry. Considering the known link between brand personality and customer purchase intent, this research sought to examine the impact of the brand personality dimension on customer buying decisions in the telec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
(83 reference statements)
2
12
0
1
Order By: Relevance
“…This method was employed to identify and address issues related to multicollinearity in the study. Contrary to concerns about common method variance, multiple studies indicated that the variance inflation factor (VIF) for the various indicators utilized in the analysis remained below the maximum threshold of ten, suggesting that common method variance was not a significant issue in these studies (Attor et al, 2022;Kumar, 2012). Assessing the discriminant validity of study variables is essential in academic research.…”
Section: Model Assessmentmentioning
confidence: 97%
“…This method was employed to identify and address issues related to multicollinearity in the study. Contrary to concerns about common method variance, multiple studies indicated that the variance inflation factor (VIF) for the various indicators utilized in the analysis remained below the maximum threshold of ten, suggesting that common method variance was not a significant issue in these studies (Attor et al, 2022;Kumar, 2012). Assessing the discriminant validity of study variables is essential in academic research.…”
Section: Model Assessmentmentioning
confidence: 97%
“…This can be seen from the peculiarities of product design. A very well-designed brand and a very well-crafted brand design produce a pleasant sense of anticipation about the brand [23]. Managers who facilitate tourists (e.g., transportation, accommodation, and up-to-date information) can convey messages in the competence indicator [24].…”
Section: The Influence Of Petengoran Mangrove Ecotourism Branding On ...mentioning
confidence: 99%
“…Indeed, brands connect with consumers through their personalities, aligning the brands with human personality attributes (Keller, 1993). Brands strongly compete to attract consumers with access to a huge amount of information through different channels and who are attracted toward brands that show their individuality (Attor et al, 2022). In the case of local brands, the reflection of consumers' identity is even more significant, with CM being crucial to express local brands' personality and individuality (Halkias et al, 2016).…”
Section: Content Marketing and Women's Happinessmentioning
confidence: 99%
“…Indeed, brands connect with consumers through their personalities, aligning the brands with human personality attributes (Keller, 1993). Brands strongly compete to attract consumers with access to a huge amount of information through different channels and who are attracted toward brands that show their individuality (Attor et al. , 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%